ANALISIS PENGELOLAAN DANA SUMBANGAN PEMBIAYAAN PENDIDIKAN (SPP) SEKOLAH (STUDI KASUS PADA SMA ISLAM BAWARI PONTIANAK) - Rahman, Aditya; Warneri, Warneri; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The school financial management process is based on school income and sources of school income Boss funds and School Committee Funds or School SPP. Apart from that, there are problems that occur, namely delays in the distribution of school tuition fees when bidding for PTS and PAS. In education financing, there is education financing planning seen from educational funding needs, for steps in managing education financing, for example education budgeting is allocated because a lot is budgeted and evaluation of the management of education financing funds is carried out every semester. The research method used is a qualitative approach-case study. The results of this research show that the process of preparing the school budget begins with a meeting with the teacher council, then the results of this meeting are used as a reference basis for making the RKAS and in accordance with the steps for preparing the budget, the implementation of school tuition fund management has two functions, namely receiving and disbursing funds, while the process The evaluation was carried out by discussing meetings between the Foundation and the school principal, treasurer and head of administration to discuss funding carried out at the end of each semester and a presentation of delays in school tuition payments of around 40-45%. This conclusion in this research has been late payment of school tuition payment of by difficult economic bills and several parent of students